Math on the Internet. - Foster, K.R.
Engineering math may have changed little since slide rules were traded in for computers, but math software continues to evolve, driven by the rapid progress of computers and by competition among software vendors. Perhaps the most interesting developments have been the emergence of new ways to publish documents containing math on the World Wide Web and the changes in math programs that have resulted. The paper considers how the evolving mathematical markup language plus add-ons to leading software are spurring computational sharing on the World Wide Web
Keywords: Internet; World Wide Web; Engineering mathematics; Mathematical markup language; Mathematics software; Software vendors